Respuesta :
Answer:
z = -26
Step-by-step explanation:
6+z/10= -2
6 + z = -2 (10)
z = -20 - 6
z = -26
![Ver imagen ricchad](https://us-static.z-dn.net/files/d99/b1b9681b596629391d52c7b1ad6589a4.png)
Answer:
z=-80
Step-by-step explanation:
multiply both sides by10
60+z=-20
z=-20-60
calculate the difference
z=-80
Answer:
z = -26
Step-by-step explanation:
6+z/10= -2
6 + z = -2 (10)
z = -20 - 6
z = -26
Answer:
z=-80
Step-by-step explanation:
multiply both sides by10
60+z=-20
z=-20-60
calculate the difference
z=-80